2015
DOI: 10.1007/jhep07(2015)078
|View full text |Cite
|
Sign up to set email alerts
|

Fast plunges into Kerr black holes

Abstract: Most extreme-mass-ratio-inspirals of small compact objects into supermassive black holes end with a fast plunge from an eccentric last stable orbit. For rapidly rotating black holes such fast plunges may be studied in the context of the Kerr/CFT correspondence because they occur in the near-horizon region where dynamics are governed by the infinite dimensional conformal symmetry. In this paper we use conformal transformations to analytically solve for the radiation emitted from fast plunges into near-extreme K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 33 publications
5
73
0
Order By: Relevance
“…We found that little changes in the fluxes during the plunge (i.e., where nonadiabatic effects are the largest) do not affect the waveform to any significant extent, because below the ISCO the motion is well approximated by a geodesic. So we expect that including nonadiabatic effects in the energy flux is not going to affect our (3,3), (3,2), (4,4), and (5,5) modes. The plots are for spin q ¼ 0.9.…”
Section: Numerical Solution Of the Time-domain Teukolsky Equationmentioning
confidence: 98%
See 4 more Smart Citations
“…We found that little changes in the fluxes during the plunge (i.e., where nonadiabatic effects are the largest) do not affect the waveform to any significant extent, because below the ISCO the motion is well approximated by a geodesic. So we expect that including nonadiabatic effects in the energy flux is not going to affect our (3,3), (3,2), (4,4), and (5,5) modes. The plots are for spin q ¼ 0.9.…”
Section: Numerical Solution Of the Time-domain Teukolsky Equationmentioning
confidence: 98%
“…4 It is relatively straightforward to estimate this discretization error: We first compute the waveforms at multiple grid resolutions, in particular we choose ðdr à ;dθÞ¼ðM=80;π=128Þ;ðM=40;π=64Þ and ðM=20; π=32Þ. Second, we derive the Richardson extrapolant using this data.…”
Section: Numerical Solution Of the Time-domain Teukolsky Equationmentioning
confidence: 99%
See 3 more Smart Citations